THE SYSTEM OF EXECUTIVE FUNCTIONS AS A NEUROPSYCHOLOGICAL CORRELATE OF TOLERANCE TO UNCERTAINTY - Lytvyn, Serhii (PSYCHOLOGICAL JOURNAL, 2018)
This article deals with the neuropsychological correlates of tolerance for uncertainty. The research focuses primarily on the study of executory functions (which are provided by the structures of the prefrontal cortex). The results of a comprehensive theoretical analysis of executing functions in the context of tolerance for uncertainty are presented. To ensure the full consideration of the executive functions as a neuropsychological correlate of tolerance to uncertainty, the adaptive value of the functions of the orbitofrontal cortex, dorsolateral cortex and ventromedial cortex was reviewed. The focus is primarily on such executive functions as planning, choosing, observing and changing behavioral strategies, ensuring spontaneity and flexibility of behavior (aspects of tolerance to uncertainty, which are provided by the dorsolateral cortex), orientation to the future and inhibition of automatic reactions (aspects of tolerance to uncertainty provided by the orbitofrontal cortex), a system of “somatic markers”, which is closely related to decision making in situations where explicit learning is compromised (dimension tolerance to uncertainty, which is provided by the operation of the ventromedial cortex). Thus, for further research on the neuropsychological correlates of uncertainty tolerance, it is suggested to focus on the executory functions of the ventromedial cortex — the system of somatic markers. Based on the theoretical analysis, it can be argued that the system of “somatic markers” is activated precisely in conditions where it is necessary to make decisions but explicit information is inaccessible (namely, adaptive solutions). The use of diagnostic techniques that have detailed instructions and substantially structured stimulus material is not recommended for studying neuropsychological correlates of tolerance for uncertainty. The main condition for a reliable diagnosis of tolerance for uncertainty is the use of psychodiagnostic techniques, including ambivalent stimuli.